Colour and textural parameters of threadfin bream surimi during frozen storage as affected by cryoprotectants and chitosan - P.T., Mathew; M., Rajalekshmi (Fishery Technology, 2025)
Effect of chitosan on the colour and textural parameters of threadfin bream surimi during frozen storage were studied in comparison to commercial cryoprotectant blend and also the suitability of chitosan to replace polyphosphate in surimi during frozen storage was analysed. The treatment with cryoprotectants and /or chitosan did not have a significant influence on the moisture levels and pH during frozen storage. The addition of chitosan or cryoprotectants did not affect the colour of the samples. The textural parameters including gel strength showed higher values for the chitosan treated samples. The samples treated with sucrose, sorbitol and polyphosphate showed higher gel strength than the control upto about 4 months of frozen storage, but the textural quality was deteriorated towards the end of frozen storage where it was inferior even to the untreated samples. The sucrose-sorbitol-chitosan blend gave better textural properties to surimi than either chitosan alone or sucrose-sorbitol-polyphosphate blend.